STRATEGI MANAJEMEN KEPALA SEKOLAH DALAM PELAKSANAAN PENDIDIKAN KARAKTER DI SD N SIDAMUKTI - Winandika, Gigih; Baro'ah, Siti (Jurnal Tawadhu, 2022)
The principal has a very important role to improve the quality of the institution he leads. As for the daily tasks of the principal, what needs to be done is to allocate more education to improve the quality of character, students, teacher and employee development, and school development, as well as provide special time to develop character education. The principal's strategy in implementing character education can also take the following steps: urging every teacher to carry out continuous professional development (PKB), a supervision schedule with the aim of helping teachers to be able to carry out the teaching process optimally. In addition, the principal's steps in strengthening character education can also use its own method, namely by direct approach with students, field surveys, student development, dealing with each student's problems directly in order to shape character more effectively.